Fungus-based synthesis of chemically difficult-to-synthesize multifunctional nanoparticles of CuAlO2 - Ahmad, Absar; Jagadale, Tushar C.; Dhas, Vivek V.; Khan, Shadab; Patil, Shankar; Pasricha, Renu; Ravi, Venkat; Ogale, Satishchandra B. (Advanced Materials, 2007)
Fungal nanosynthesis of ternary CuAlO2 phase is achieved at 50 degrees C. This phase is chemically difficult to synthesize at low temperatures because of the incompatible oxidation chemistry of Cu and Al. The synthesized protein-capped water-dispersible nanoparticles show blue luminescence and radio-frequency absorption (see figure).

Ferroelectric and electrical characterization of multiferroic BiFeO3 at the single nanoparticle level - Vasudevan, R. K.; Bogle, Kashinath A.; Kumar, A.; Jesse, S.; Magaraggia, R.; Stamps, R.; Ogale, Satishchandra B.; Potdar, H. S.; Nagarajan, V. (Applied Physics Letters, 2011)
Ferroelectric BiFeO3 (BFO) nanoparticles deposited on epitaxial substrates of SrRuO3 (SRO) and La1-xSrxMnO3 (LSMO) were studied using band excitation piezoresponse spectroscopy (BEPS), piezoresponse force microscopy (PFM), and ferromagnetic resonance (FMR). BEPS confirms that the nanoparticles are ferroelectric in nature. Switching behavior of nanoparticle clusters were studied and showed evidence for inhomogeneous switching. The dimensionality of domains within nanoparticles was found to be fractal in nature, with a dimensionality constant of similar to 1.4, on par with ferroelectric BFO thin-films under 100 nm in thickness. Ferromagnetic resonance studies indicate BFO nanoparticles only weakly affect the magnetic response of LSMO. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3671392]

Ferromagnetism in metal oxide systems: interfaces, dopants, and defects - Thakare, Vishal P.; Game, Onkar S.; Ogale, Satishchandra B. (Journal of Materials Chemistry C, 2013)
Ferromagnetism in metal oxide systems has always attracted scientific attention in view of the intriguing and interesting interplay of spin, charge, orbital and lattice degrees of freedom that such systems display. This trend appears to be continuing with enhanced focus on interface systems, multiferroics, diluted magnetic semiconducting oxides (DMSOs) and nanomaterial magnetism. Newer techniques are being applied to bring out materials issues that are critical to the precise understanding of the origin of magnetism in certain cases. Interest is also beginning to grow in exploring application potential of some such systems. In this article we review the developments in this field by late 2011 and 2012.